DAMPAK EL NINO TERHADAP PENDAPATAN RUMAH TANGGA PETANI PADI DI KECAMATAN PUNGGUR, KABUPATEN LAMPUNG TENGAH - Nopralita Nopralita; Zainal Abidin; Muhammad Irfan Affandi (Lampung University, 2017)
This research at was understanding the impact of El Nino on production, income of rice farmer, efficiency in the use of production factors and finding out farmers mitigation in facing El Nino season. The study was undertaken in Punggur Sub-district of Center Lampung District. Which was chosen pusposively. The sample size was 36 near from irrigation facilities and 40 far from irrigation facilities and were collected from March to April 2016 and using difference of production; difference ofincome of rice farmer; mitigation analysist. The study showed that during El Nino, there is a significant difference between rice production near and far from irrigation facilities, where as during El Nino rice production downed by 8,32 percent (far from irrigation) and 5,54 percent (near from irrigation), during El Nino,there is a significant difference between income of rice farmer near and far from irrigation facilities, where as during El Nino income downed by 3,24 percent (far from irrigation) and 7,98 percent (near from irrigation) during El Nino, farmer do some mitigation such as using water pump but with schedule adding production facilities and changing cropping pattern and varieties. Key words : houasehold income, impact of el nino, rice farmer